Introduction to the fourth regular issue of JALT (Journal of Applied Learning and Teaching, 2019)
The end of the year – and the dubitable (more on this shortly) close of the decade – invites us to be more philosophical than we usually allow ourselves to be in the hustle-and-bustle of the everyday lives of teachers. It is indeed debatable whether the end of 2019 marks the end of a decade. By the time you read these lines, the 2020s may or may not have started, even when applying the Gregorian calendar (and not another calendar, for instance, the Chinese, Islamic or Thai solar calendar, to mention but a few). The year 1 BC was followed by 1 AD (shockingly, there was no year 0 Anno Domini), and as a consequence, the third millennium and 21st century started in 2001, rather than in 2000. While mathematically, the new decade should only start in 2021, convention tells us that 1 January, 2020, marks the beginning of the new decade. And while we write these lines in the old decade, the jury is still out how to call the 2010s – the ‘tens’, ‘twenty-tens’, ‘two-thousand-tens’ or even ‘teens’, ‘teenies’, ‘teensies’, ‘tensies’, or ‘ten-sions’. Time will tell.If a simple matter like the above calendrical confusion already seems less-than-certain, uncertainty is certainly something that engulfs more complex matters. Falsification has shattered gospel truths. Today, we know that not all swans are white, but people in the Old World certainly thought so till Australia and her black swans were discovered. Inductive reasoning and generalising have long become problematic, knowledge fragile, and Nassim Nicholas Taleb’s book The black swan. The impact of the highly improbable a celebrated bestseller.